Hello to the cannibals a novel - Bausch, Richard 1945- (HarperCollinsPublishers, 2002)
Pregnant, newly married, and living with her in-laws, Lily Austin writes a play about famed nineteenth-century British explorer Mary Kinglsey and finds inspiration in her subject's writings.